#### Answer

$x=\frac{22}{9}$
$y=\frac{22}{3}$

#### Work Step by Step

First, we have to solve the second equation for $y$ and after that, we can substitute this expression in the first equation:
$-3x+y=0$
$y=3x$
$3x-4y=-22$
$3x-4(3x)=-9x=-22$
$x=\frac{22}{9}$
$3x=y=3\frac{22}{9}=\frac{22}{3}$
We need to check, if it is the right solution, we substitute x with $\frac{10}{7}$ and y with $-\frac{5}{7}$:
$3(\frac{22}{9})-4(\frac{22}{3})=\frac{-66}{3}=-22$ $\checkmark$
$-3\frac{22}{9}+(\frac{22}{3})=0$ $\checkmark$